Future challenges in gastroenterology and hepatology, between innovations and unmet needs: A SIGE Young Editorial Board's perspective. Issue 5 (May 2022) - Losurdo, Giuseppe; Gravina, Antonietta Gerarda; Maroni, Luca; Gabrieletto, Enrico Maria; Ianiro, Gianluca; Ferrarese, Alberto; ,; Visintin, Alessia; Frazzoni, Leonardo; Pellegatta, Gaia; Sessa, Anna; Lopetuso, Loris; et al.
Abstract: Gastroenterology, Digestive Endoscopy and Hepatology have faced significant improvements in terms of diagnosis and therapy in the last decades. However, many fields still remain poorly explored, and many questions unanswered. Moreover, basic-science, as well as translational and clinical discoveries, together with technology advancement will determine further steps toward a better, refined care for many gastroenterological disorders in the future. Therefore, the Young Investigators of the Italian Society of Gastroenterology (SIGE) joined together, offering a perspective on major future innovations in some hot clinical topics in Gastroenterology, Endoscopy, and Hepatology, as well as the current pitfalls and the grey zones.